Change of Morphological Characters of an Introduced Population of Bilih Fish (Mystacoleucus padangensis Bleeker, Pisces: Cyprinidae) in Toba Lake - Nofrita nofrita; Dahelmi dahelmi; Hafrijal Syandri; Djong Hon Tjong (Universitas Andalas, 2019)
Population of Bilih Fish (Mystacoleucus padangensis) in Singkarak Lake has decreased as the effect of intensive exploitation and changes in water use function. Many appropriate works have been conducted for the fish conservation. One of them is introducing Bilih fish population to a new habitat, Toba Lake. After nine years of releasing the fish, there was a hypothesis that these fish had undergone some changes on their morphology compared to their original population in Singkarak Lake. The changes could occure in some morphological characters and also the increase or decrease of their growth. This study was aimed at comparing morphology characters between Bilih fish introduced to Toba Lake with the original population in Singkarak Lake. Survey method was used and 400 samples of fish were taken from each Singkarak and Toba Lakes. Parameters measured were 29 morphological characters. Data were analyzed using Mann Whitney U Test with SPSS 22. The results showed that 27 morphological characters of introduced fish had changed. Characters that had not changed were dorsal fin (anterior end)-anal fin distance (DFAF) and preanal distance (PD). Population of Bilih fish in Toba Lake might keep changing in the process of morphological character differentiation as long as environment factors still support the life of Bilih fish.